Behavioural and cognitive changes induced by Toxoplasma gondii and its pathological development in wistar rats - Che Omar, Siti Shafiyyah (2017)
Objective: This study aimed to identify the behavioural and cognitive changes induced by Toxoplasma gondii and its pathological development in Wistar rats. Methodology: Study involved the in vivo test that was conducted by using Toxoplasma gondii RH strain on rats to perform the behavioral tests. Locomotor activity in Open-Field Test (OFT), anxiety study in Elevated-Plus Maze (EPM) and working memory study in Novel Object Discrimination test (NOD) were performed for the determination of toxoplasmosis profile on animal model. Thirty five male Wistar rats were used in the study and divided into five groups which were control group (negative control), Toxoplasma-infected group and three groups of positive control; Amphetamine, Diazepam, Scopolamine. All dosage administrated orally gavages to each rats in the control and T. gondii groups on the first day and profile behavioral test was performed after a six weeks. After the completion of behavioral study, rats were sacrificed and their brain, liver and kidney were collected to evaluate any morphological changes through histopathological examination. DNA extraction of samples (Formalin-fixed paraffin embedded) were conducted and followed by polymerase chain reaction (PCR) amplification of T. gondii B1 gene. Results: This study showed that there was a significant difference of mean score of gridline in locomotor activity; thirty minutes (counts) of crossing the gridline at the p<0.05 level among the three groups F (2, 15) = 10.548, p=0.001. In anxiety study, two parameters were performed on each rat; time spent in open arms and open arm entries frequency. Toxoplasma-infected group showed significant increases in both of open arm time spent and open arm entries frequency compared with control group. In Novel Object Discrimination test, the result revealed that there was a significant difference in exploration time (mean time spent ) on the familiar object (A3) and novel object (B) in control group for exploration time, from A3 (M = 0.04, SD = 0.03) to B (M = 0.07, SD = 0.05), t (4) = -2.92, p < 0.04. Both discrimination index and discrimination ratio show significant difference between three groups; F (2, 12) = 5.734, p=0.018; F (2, 12) = 5.962, p=0.016. Histopathological examination revealed that the morphological of appearance of lesions on the brain was identified in Toxoplasma-infected group. Meanwhile in control group no lesions were detected (normal). Through the molecular study (PCR) it was confirmed the presence of T. gondii in the tissue sample. Conclusion: T. gondii RH strain in Wistar rats was demonstrated to cause hyperactivity in locomotor; memory deficit in novel object discrimination and reflect the less anxiety by entering more entries and time spent in open arm. It is clear that Toxoplasma gondii infection reflects the behavior profiles on the host. Due to the specific strains and species of host; RH strain is virulent strain giving less potential to produced cysts in the brain and higher sensitivity and specificity of PCR yielded the desired positive outcomes of 301 base pair B1 gene of Toxoplasma gondii.